The Non-uniform School Education System in India: A Critical Analysis: Addressing Inequalities in the Indian School Education System (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Introduction Education is a dynamic force in the life of every individual, influencing his physical, mental, emotional, social and ethical developments. India has a long history of organized education. The Gurukul system of education is one of the oldest in India and it is not for all. The current system of education, based on western style and it is for all. The multi-dimensional growth of a nation is dependent on the presence of qualified and dynamic human resources. The greater the proportion of qualified human resources, the greater the contribution of this population in making a country develop holistically. It is the presence of quality education that propels individuals and, in turn, nations to attain economic goals, and maintain sustainable growth with equity by providing the fruits of development for all. The present school education system is mainly of three types such as levels of education, ownership of educational institutions and educational board affiliations. The present paper focuses on ownership and boards of educational institutions. These two factors are providing non-uniform education in India. It leads to major inequalities among the students. The medium of instruction as an English is one of the drawbacks in the accessing quality education among students. Methodology The present study, which is based on secondary data. Conclusion The condition of the education system, especially school education is not better condition, because of dividing ownership of educational institutions and educational board affiliations. These are the major disadvantages to get a uniform education. There is, therefore, a need to develop a system that can provide an equal opportunity for every citizen of the country for the development of the individual in particular and society in general.